Peningkatan Hasil Belajar IPA Menggunakan Pendekatan Konstruktivisme di Kelas IV Sekolah Dasar - Lianti, Wiwit; F, Farida; Maimunah, Maimunah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research was intended to improve the studens’ learning achievement in the Social Studies by using Problem-Based Learning model in the fourth grade of  SDN 04 Sintuk Toboh Gadang Kabupaten Padang Pariaman. This was a classroom action research which used qualitative and quantitative approaches. The subject of the research was the fourth grade students of  SDN 04 Sintuk Toboh Gadang. Based on the result of data analysis, it was figured out that from the first cycleto the second one, the average score for the Lesson Plan improved from 67,83% into 87,49%, the teacher’s aspect improved from 85,71%, and the student’s aspect improved from 64,28% into 87,26%. In addition, the student’s learning achievement improved from 69,5% into 92,5%%.  Katakunci: hasilBelajar IPA, Pendekatan Konstruktivisme